CEO Successor Characteristics and the Choice of Foreign Market Entry Mode: An Empirical Study - Herrmann, Pol; Datta, Deepak K. (Journal of International Business Studies, 2002)
Based on the upper echelons theory, this study of 126 CEO successions and 271 foreign market entry events examines the relationships between successor CEO characteristics and choice of entry mode. Results indicate that CEO position tenure, throughput functional background, and international experience are associated with full-control entry modes. Additionally, these relationships were observed in the subgroup of high-performing firms but not in the low-performing subgroup.